2020
DOI: 10.1039/d0na00098a
|View full text |Cite
|
Sign up to set email alerts
|

On-site growth method of 3D structured multi-layered graphene on silicon nanowires

Abstract: A well-controlled sheet of multilayer graphene is grown on-site to conform to the shape of an underlying silicon nanowire substrate and which may be used in future photovoltaic device applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…They showed that the pulverization phenomenon observed in the Si anode was effectively delayed using the as-fabricated core/shell nanocomposite anode. In addition, it was reported that the Si/CNT core/shell nanocomposites were successfully fabricated by depositing graphene on Si nanowires (SiNWs) [ 12 , 13 ]. Therefore, the Si/CNT core/shell nanocomposite electrode model is promising for application in LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the pulverization phenomenon observed in the Si anode was effectively delayed using the as-fabricated core/shell nanocomposite anode. In addition, it was reported that the Si/CNT core/shell nanocomposites were successfully fabricated by depositing graphene on Si nanowires (SiNWs) [ 12 , 13 ]. Therefore, the Si/CNT core/shell nanocomposite electrode model is promising for application in LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Through our group's work with silicon nanowires (SiNWs), [25][26][27] it was observed that metal thin lms will easily form particles on the top of cylindrical nanowires. This was suspected to be due to the SiNW surface geometry's effect on the metal thin lm surface energy.…”
Section: Introductionmentioning
confidence: 99%